DYNAMICS OF FORESTRY REGULATIONS IN THE ERA OF DECENTRALIZATION: CHALLENGES OF HARMONIZATION BETWEEN CENTRAL AND REGIONAL GOVERNMENTS - Moh. Arief Erawan; Mohamad Rasyid Ridho; Muslim A. Kasim; Sarfan Tabo (PT. Radja Intercontinental Publishing, 2026)
orestry policy-making and implementation in Indonesia. Forestry regulations, which are intended to provide a strong legal foundation for sustainable forest governance, instead reveal a growing disconnect between centrally issued norms and their implementation at the local level. Overlapping authorities, regulatory disharmony, and unclear institutional roles between different levels of government have created persistent legal and administrative challenges, undermining effective forest management and environmental protection. This article examines these dynamics and highlights the need for harmonization between central and regional regulations. Using a normative juridical approach, the study analyzes constitutional provisions, statutory regulations, and legal doctrines governing the distribution of authority in the forestry sector. The findings affirm the urgency of restructuring legal authority and aligning sectoral norms with the principles of decentralization, legal certainty, good governance, and environmental sustainability. Strengthening regulatory coherence and clarifying institutional responsibilities are essential to improving the effectiveness of forestry governance and ensuring sustainable forest management in Indonesia.